Reference gene and small RNA data from multiple tissues of Davidia involucrata Baill - Yang, Hua (Sci Data, 2019)
Davidia involucrata Baill. is a rare plant endemic to China. Its exclusive evolutionary position and specific floral organs endow it with a high research value. However, a lack of genomic resources has constrained the study of D. involucrata functional genomics. Here, we report D. involucrata transcriptome reads from different floral tissues pooled from six individuals at two developmental stages using Illumina HiSeq technology and the construction of a high-quality reference gene set containing a total of 104,463 unigenes with an N50 of 1,693 bp and 48,529 high-quality coding sequences. The transcriptome data exhibited 89.24% full-length completeness with respect to the benchmarking universal single-copy (BUSCO) dataset and a PLAZA CoreGF weighted score of 98.85%. In total, 65,534 (62.73%) unigenes were functionally annotated, including 58 transcription factor families and 44,327 simple sequence repeats (SSRs). In addition, 96 known and 112 novel miRNAs were identified in the parallel small RNA sequencing of each sample. All these high-quality data could provide a valuable annotated gene set for subsequent studies of D. involucrata.